Internasjonaliseringen av StatoilHydro : hendelser og faktorer som har preget StatoilHydros ønske om internasjonal suksess - Fløystad, Hans-Martin (Høgskolen i Bodø, 2008)
Mastergradsoppgave i bedriftsøkonomi - Høgskolen i Bodø, 2008 Abstract Internationalization of companies has become a gradually more growing trend in today’s modern and technological world. The Norwegian oil company StatoilHydro, has trough the last 18 years focused heavily on getting their business abroad, to become an internationally recognized multinational oil company. Strategic alliances and collaborations have been key strategies in StatoilHydros effort to reach their international goals. The objective of this research paper is to identify which critical events that StatoilHydro has been trough in their effort to be a significant multinational company and how sustainable development is increasingly becoming a key factor in their quest for international success. Via a strategic alliance with British Petroleum, Statoil (which was the companys name back then) took the first big step in the internationalization process during the early 1990s. This step has been followed up with a part-privatization of the company through a listing of their stocks in 2001 to become a fixture on the stock exchange. A joint venture that created Statoil Detaljhandel, after a partnership between ICA and Statoil, brought Statoil into the daily groceries business in Scandinavia. The merger between Statoil and Hydro, which led to a change in name to StatoilHydro, created an oil- and gas company which has a market value that can be compared with some of the major companies in the oil industry. The merger is so far the last big step that has been made from Statoil to increase its chances of success abroad. Through an increasing focus on sustainable development, StatoilHydro has had up and downs during the company’s efforts in Angola, Aserbajdsjan and Iran. StatoilHydro has not backed down though and continues their mission to have sustainable development as a key factor for their efforts abroad.